2009
DOI: 10.3758/lb.37.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning in human and nonhuman animals: A search for common ground

Abstract: Perceptual learning has been extensively studied in both human and nonhuman animals, but the two lines of research have, for the most part, developed independently, addressing seemingly rather different issues by rather different methods. It has been argued, however, that analysis of the disparate phenomena studied in experiments on perceptual learning reveals that in all the studies, the essential feature is that appropriate training allows behavior to come to be controlled by the unique features, rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 30 publications
1
22
0
2
Order By: Relevance
“…They have shown that if rats are exposed to AX and X in alternation and, in a separate block of trials, to CX, subsequent conditioning proceeds more rapidly to A than to C. Intermixed exposure to AX and X preserves the salience of A, whose representation is retrieved on the intervening X-alone trials, whereas no such effect is observed to C after a block of CX exposure trials. Other studies have revealed some problems for this interpretation Hall & Rodriguez, in press), and I think I can safely leave it to Hall's own contribution to this symposium (Hall, 2009) to make the case for his account. But, as was noted by Dwyer and Honey, most of these findings can probably also be derived from the McLaren and Mackintosh (2000) model.…”
Section: Explanations Of Unsupervised Perceptual Learning In Animalsmentioning
confidence: 87%
“…They have shown that if rats are exposed to AX and X in alternation and, in a separate block of trials, to CX, subsequent conditioning proceeds more rapidly to A than to C. Intermixed exposure to AX and X preserves the salience of A, whose representation is retrieved on the intervening X-alone trials, whereas no such effect is observed to C after a block of CX exposure trials. Other studies have revealed some problems for this interpretation Hall & Rodriguez, in press), and I think I can safely leave it to Hall's own contribution to this symposium (Hall, 2009) to make the case for his account. But, as was noted by Dwyer and Honey, most of these findings can probably also be derived from the McLaren and Mackintosh (2000) model.…”
Section: Explanations Of Unsupervised Perceptual Learning In Animalsmentioning
confidence: 87%
“…Mackintosh (2009) quotes Fahle's (2002, p. ix) definition, according to which perceptual learning "improves discrimination between stimuli that could not be discriminated before learning." Hall's (2009) definition of perceptual learning (originally stated in Hall, 2008) is very similar to Mackintosh's, but also hints at a mechanism by which improved discrimination might come about. Hall says that perceptual learning is "the learning process (or processes) that increases the effectiveness of the unique stimulus elements and/or reduces that of common stimulus elements, thus facilitating discrimination between similar stimuli" (p. 135).…”
mentioning
confidence: 77%
“…The intermixed-blocked effect has received a great deal of attention recently because it cannot be explained in terms of the relative exposure to (and therefore familiarity of) the common and unique features; this is equivalent in the intermixed and blocked conditions. Nevertheless, three of the four theories that have been proposed to account for the intermixed-blocked effect (see Mackintosh, 2009)-and much of the data (e.g., Blair & Hall, 2003;Mitchell, Kadib, et al, 2008)-suggest that the unique features A and B are more salient following intermixed than following blocked preexposure (see Hall, 2009). …”
Section: The Associative Analysis Of Perceptual Learningmentioning
confidence: 99%
See 2 more Smart Citations